TINGKAT KESIAPAN GURU PJOK DI SMA NEGERI OLAHRAGA PROVINSI RIAU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA - Ardiansyah, Ardiansyah; Vai, Aref; Rahmatullah, M. Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to determine the level of readiness ofPJOK teachers at Public High School Sports in Riau Province in implementing theindependent curriculum. This research is quantitative descriptive research used to solveor answer a problem that is being faced in the current situation. The method used in thisresearch uses a survey method. This research was planned at SMA Negeri Sport Jl. YosSudarso, Damai Valley, District. Coastal Rumbai, Pekanbaru City. This research wasplanned after examining the proposal and receiving research approval. This researchshows that the level of readiness of PJOK teachers at the Riau Province Sports HighSchool in implementing the Merdeka Curriculum is in a fairly good category, withdetails of 33.3% very ready and 66.7% ready. Even though there are no teachers whoare in the sufficiently prepared category, these results show that the majority ofteachers already have adequate readiness to face the implementation of the Independent Curriculum. However, there are still obstacles in using facilities and infrastructure as well as understanding teaching materials that are in accordance with the Independent Curriculum.Key Words: PJOK Teacher Readiness, Independent Curriculum